1985
DOI: 10.5014/ajot.39.1.11
|View full text |Cite
|
Sign up to set email alerts
|

Shoulder Pain in Hemiplegia

Abstract: Development of a painful shoulder in the hemiplegic patient is a significant and serious problem, because it can limit the patient's ability to reach his or her maximum functional potential. Several etiologies of shoulder pain have been identified, such as immobilization of the upper extremity, trauma to the joint structures, including brachial plexus injuries, and subluxation of the gleno-humeral joint. A review of the literature explains the basic anatomy and kinesiology of the shoulder complex, the various … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
55
0
1

Year Published

1987
1987
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(57 citation statements)
references
References 15 publications
0
55
0
1
Order By: Relevance
“…This muscle activity may be absent when flaccidity occurs after a stroke (Andersen, 1985). Chaco and Wolf (1971) found that subluxation developed within several weeks after a stroke when the arm was flaccid and that normal muscle contraction did not occur in response to loading.…”
mentioning
confidence: 99%
See 3 more Smart Citations
“…This muscle activity may be absent when flaccidity occurs after a stroke (Andersen, 1985). Chaco and Wolf (1971) found that subluxation developed within several weeks after a stroke when the arm was flaccid and that normal muscle contraction did not occur in response to loading.…”
mentioning
confidence: 99%
“…The causes of inferior subluxation after stroke are unclear, although many factors have been proposed as contributory (Andersen, 1985;Basmajian & Bazant, 1959;Ikai, Tei, Yoshida, Miyano, & Yonemoto, 1998;Moskowitz, Goodman, Smith, Balthazar, & Mellins, 1969;Runyan, 1995). In approximately 90% of patients early poststroke, the affected extremity is initially flaccid (Moskowitz et al, 1969).…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…62,63 Following stroke, in the absence of muscle function, soft tissues such as the joint capsule and ligaments provide protection and support to the shoulder joint but only for a limited period of time. 64,65 Gradually, the weight of the arm under the influence of gravity causes the capsule to stretch, leading to inferior subluxation, 4,25 which becomes apparent when the patient is in a gravitydependent position. Activation of shoulder muscles, therefore, has been a key therapeutic intervention in the clinical management of subluxation.…”
Section: Motor Recoverymentioning
confidence: 99%